K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 7 2021

a) A=(4-5x)2-(3+5x)2=(4-5x-3-5x)(4-5x+3+5x)=(-25x+1)1=-25x+1

26 tháng 7 2021

B=(3x-1)(1+3x)-(3x+1)2=9x2-1-(3x+1)2=9x2-1-(9x2+6x+1)=9x2-1-9x2-6x-1=-6x-2=-2(3x+1)

24 tháng 11 2021

\(a,=16x^8+8x^6\\ b,=4x^4-6x^5-4x^3\\ c,=15x^6+9x^3y-10x^3y-6y^2\\ =15x^6-x^3y-6y^2\\ d,=2a^4-a^3b+6a^2b-3ab^2-3ab^2+b^3\\ =2a^4-a^3b+6a^2b-6ab^2+b^3\)

24 tháng 7 2018

c,4x2-20x+25-4x2-20x-25+40x-1

=-1

4 tháng 9 2019

A= (6x-2)^2 + (2-5x)^2+2(6x-2)(2-5x)

= (6x-2)^2 +2(6x-2)(2-5x)+ (2-5x)^2

\(=\left(6x-2+2-5x\right)^2=x^2\)

B= (2a^2+2a+1)(2a^2-2a+1)-(2a^2+1)^2

\(=\left(2a^2+1\right)^2-4a^2-\left(2a^2+1\right)^2=4a^2\)

C=(x+3)(x^2-3x+9)-(54+x^3)

\(=\left(x^3+27\right)-54-x^3=27\)

D=(2x+y)(4x^2-2xy+y^2)-(2x-y)(4x^2+2xy+y^2)

\(=\left(2x+y\right)^3-\left(2x-y\right)^3\)

E=(a+b)^2-(a-b)^2

\(=\left(a+b+a-b\right)\left(a+b-a+b\right)=2a.2b=4ab\)

4 tháng 9 2019

Secret Personv: thật.CTV lạ z

\(C=\left(x+3\right)\left(x^2-3x+9\right)-\left(54+x^3\right)\)

\(=x^3-27-54-x^3=-81\)

26 tháng 7 2020

(3x^3 - 2x^2 + x + 2)(5x^2)

= 15x^5 - 10x^4 + 5x^3 + 10x^2

(3x^2 + 5x - 2)(2x^2 - 4x + 3)

= 3x^4 - 12x^3 + 9x^2 + 10x^3 - 20x^2 + 15x - 4x^2 + 8x - 6

= 6x^4 - 2x^3 - 15x^2 + 23x - 6